Data.Monoid

The plain source file for module Data.Monoid is not available.
-----------------------------------------------------------------------------
-- |
-- Module      :  Data.Monoid
-- Copyright   :  (c) Andy Gill 2001,
-- 		  (c) Oregon Graduate Institute of Science and Technology, 2001
-- License     :  BSD-style (see the file libraries/base/LICENSE)
-- 
-- Maintainer  :  libraries@haskell.org
-- Stability   :  experimental
-- Portability :  portable
--
-- The Monoid class with various general-purpose instances.
--
--	  Inspired by the paper
--	  /Functional Programming with Overloading and
--	      Higher-Order Polymorphism/, 
--	    Mark P Jones (<http://www.cse.ogi.edu/~mpj/>)
--		  Advanced School of Functional Programming, 1995.
-----------------------------------------------------------------------------

module Data.Monoid (
 	Monoid(..),
	Dual(..),
	Endo(..),
	All(..),
	Any(..),
	Sum(..),
	Product(..)
  ) where

import Prelude

-- ---------------------------------------------------------------------------
-- | The monoid class.
-- A minimal complete definition must supply 'mempty' and 'mappend',
-- and these should satisfy the monoid laws.

class Monoid a where
	mempty  :: a
	-- ^ Identity of 'mappend'
	mappend :: a -> a -> a
	-- ^ An associative operation
	mconcat :: [a] -> a

	-- ^ Fold a list using the monoid.
	-- For most types, the default definition for 'mconcat' will be
	-- used, but the function is included in the class definition so
	-- that an optimized version can be provided for specific types.

	mconcat = foldr mappend mempty

-- Monoid instances.

instance Monoid [a] where
	mempty  = []
	mappend = (++)

instance Monoid b => Monoid (a -> b) where
	mempty _ = mempty
	mappend f g x = f x `mappend` g x

instance Monoid () where
	-- Should it be strict?
	mempty        = ()
	_ `mappend` _ = ()
	mconcat _     = ()

instance (Monoid a, Monoid b) => Monoid (a,b) where
	mempty = (mempty, mempty)
	(a1,b1) `mappend` (a2,b2) =
		(a1 `mappend` a2, b1 `mappend` b2)

instance (Monoid a, Monoid b, Monoid c) => Monoid (a,b,c) where
	mempty = (mempty, mempty, mempty)
	(a1,b1,c1) `mappend` (a2,b2,c2) =
		(a1 `mappend` a2, b1 `mappend` b2, c1 `mappend` c2)

instance (Monoid a, Monoid b, Monoid c, Monoid d) => Monoid (a,b,c,d) where
	mempty = (mempty, mempty, mempty, mempty)
	(a1,b1,c1,d1) `mappend` (a2,b2,c2,d2) =
		(a1 `mappend` a2, b1 `mappend` b2,
		 c1 `mappend` c2, d1 `mappend` d2)

instance (Monoid a, Monoid b, Monoid c, Monoid d, Monoid e) =>
		Monoid (a,b,c,d,e) where
	mempty = (mempty, mempty, mempty, mempty, mempty)
	(a1,b1,c1,d1,e1) `mappend` (a2,b2,c2,d2,e2) =
		(a1 `mappend` a2, b1 `mappend` b2, c1 `mappend` c2,
		 d1 `mappend` d2, e1 `mappend` e2)

-- lexicographical ordering
instance Monoid Ordering where
	mempty         = EQ
	LT `mappend` _ = LT
	EQ `mappend` y = y
	GT `mappend` _ = GT

-- | The dual of a monoid, obtained by swapping the arguments of 'mappend'.
newtype Dual a = Dual { getDual :: a }

instance Monoid a => Monoid (Dual a) where
	mempty = Dual mempty
	Dual x `mappend` Dual y = Dual (y `mappend` x)

-- | The monoid of endomorphisms under composition.
newtype Endo a = Endo { appEndo :: a -> a }

instance Monoid (Endo a) where
	mempty = Endo id
	Endo f `mappend` Endo g = Endo (f . g)

-- | Boolean monoid under conjunction.
newtype All = All { getAll :: Bool }
	deriving (Eq, Ord, Read, Show, Bounded)

instance Monoid All where
	mempty = All True
	All x `mappend` All y = All (x && y)

-- | Boolean monoid under disjunction.
newtype Any = Any { getAny :: Bool }
	deriving (Eq, Ord, Read, Show, Bounded)

instance Monoid Any where
	mempty = Any False
	Any x `mappend` Any y = Any (x || y)

-- | Monoid under addition.
newtype Sum a = Sum { getSum :: a }
	deriving (Eq, Ord, Read, Show, Bounded)

instance Num a => Monoid (Sum a) where
	mempty = Sum 0
	Sum x `mappend` Sum y = Sum (x + y)

-- | Monoid under multiplication.
newtype Product a = Product { getProduct :: a }
	deriving (Eq, Ord, Read, Show, Bounded)

instance Num a => Monoid (Product a) where
	mempty = Product 1
	Product x `mappend` Product y = Product (x * y)

Index

(HTML for this module was generated on 2013-09-19. About the conversion tool.)